2008
DOI: 10.1007/s00520-007-0384-y
|View full text |Cite
|
Sign up to set email alerts
|

Changes in quality of life and its related factors in liver cancer patients receiving stereotactic radiation therapy

Abstract: Liver cancer patients had stable and moderate levels of QOL during SRT. Factors related to QOL across the 6 weeks were multi-dimensional. Both overall symptom severity and selected individual symptoms were important to patients' QOL. These factors should all be carefully assessed and clinically treated to enhance liver cancer patients' QOL during SRT.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
19
1
3

Year Published

2010
2010
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(28 citation statements)
references
References 28 publications
2
19
1
3
Order By: Relevance
“…This study also found that there appears to be differences in the reporting of PWB, EWB, and overall QOL between cancer diagnosis groups. Those diagnosed with breast cancer reported higher PWB and overall QOL scores but lower EWB score compared with those with liver cancer, for liver cancer patients often suffer multiple symptoms that may have a negative effect on overall QOL, especially physical well-being [36,37], while breast cancer patients usually feel angry, anxious or distressful, and other negative moods due to loss of body image [38]. Additionally, treatment-related variables such as previous treatments and the number of kinds of previous treatments appeared to be meaningful factors for explaining the variance in PWB and FWB.…”
Section: Itemmentioning
confidence: 97%
“…This study also found that there appears to be differences in the reporting of PWB, EWB, and overall QOL between cancer diagnosis groups. Those diagnosed with breast cancer reported higher PWB and overall QOL scores but lower EWB score compared with those with liver cancer, for liver cancer patients often suffer multiple symptoms that may have a negative effect on overall QOL, especially physical well-being [36,37], while breast cancer patients usually feel angry, anxious or distressful, and other negative moods due to loss of body image [38]. Additionally, treatment-related variables such as previous treatments and the number of kinds of previous treatments appeared to be meaningful factors for explaining the variance in PWB and FWB.…”
Section: Itemmentioning
confidence: 97%
“…This constitutes preliminary evidence of the existence of co-occurring symptoms in patients with sleep disturbance, which is consistent with the literature on hepatocellular carcinoma patients undergoing TACE treatment. 6,7,17 The evidence related to sleep disturbance in hepatocellular carcinoma patients undergoing TACE treatment calls for advanced research in this area. Our research revealed patients' experience with sleep disturbance, as well as determinants, consequences, and potential interventions.…”
Section: The Determinants Of Presence or Absence Of Sleep Disturbancementioning
confidence: 99%
“…6,7,17,31 Fatigue was identified as one of the most common problems and most important predictors of sleep disturbance. Although the findings of different studies are consistent, the cause-and-effect relationships between fatigue and sleep disturbance are unclear.…”
Section: The Determinants Of Presence or Absence Of Sleep Disturbancementioning
confidence: 99%
See 1 more Smart Citation
“…1 summarizes the review process. Of 2181 initially screened studies, 4 met all inclusion criteria (Klein et al, Shun et al, Mendez Romero et al, Thibault et al) and were analysed, with one additional study having met criteria after being identified from a grey literature search (Law et al) [1822].
Fig.
…”
Section: Resultsmentioning
confidence: 99%